Impact of a Structured Educational Program on Awareness of the Human Papilloma Virus Vaccine for Cervical Cancer Prevention Among Women in a Chosen Rural Region of Rajkot - Usha Devi S.; Mira Vala (International Journal of Oncological Nursing and Practices, 2024)
The World Health Organization (WHO) advocates for the inclusion of the human papilloma virus (HPV) vaccine in standard immunization schedules worldwide, in addition to other preventive strategies. The launch of the prophylactic HPV vaccine has markedly improved primary prevention measures against cervical cancer and other diseases caused by HPV. Following their approval in 2006, both the quadrivalent and bivalent HPV vaccines have received authorization in over 100 countries. As of the start of 2012, the HPV vaccine was incorporated into the national vaccination schedules of a minimum of 40 countries worldwide. The vaccine regimen consists of two or three doses, depending on the recipient's age and immune function. Despite vaccination, cervical cancer screening remains essential. Widespread vaccination not only protects vaccinated individuals but also confers indirect benefits to those not vaccinated. The HPV vaccines are considered highly safe, though common side effects, affecting about 80% of recipients, include pain, redness at the injection site, and fever. The main purpose of the HPV vaccine is to provide protection against cervical cancer. It has also been shown to block almost 100% of the precancerous changes in cervical cells linked to HPV types 16 and 18. According to available information, the duration of protection for Cervarix extends up to 6.4 years, while for Gardasil, it lasts up to 5 years in women who tested negative for HPV at the moment of vaccination. The present pre-experimental one group pretest and posttest research design was conducted among women to evaluate the effectiveness of HPV vaccine for prevention of cervical cancer. The researcher selected 60 samples based on nonprobability sampling technique. The findings indicated that knowledge levels improved following the implementation of a structured teaching program, demonstrating its effectiveness. The researcher concluded that, the teaching aids will be helpful in improving knowledge among women as well as public. The researcher recommended that, the community education program and personal behavior change education is required for bring awareness regarding HPV vaccine for prevention of cervical cancer.
Keywords: Human papilloma virus vaccine; Immune response; cervical cancer; sampling technique; women